(untitled) (Research, Society and Development, 2022)
Endophytic fungi are microorganisms that live inside plants, establishing a mutualistic relationship, where both benefit from this interaction. They require protection and nutrients from host plants, and in return fungi can contribute to host’s growth and nutrient uptake. In addition, they can improve plant tolerance to abiotic and biotic stresses and increase plant resistance to insects and pests. Endophytic fungi produce bioactive compounds similar to those of the host plant. The economic exploitation of these bioactive compounds is much promising. These bioactive products are related to sustainable production systems and to the development of new substances with strong pharmacological properties such as antiviral, antifungal, anti-inflammatory, antitumor and antiparasitic, antidiabetic and immunosuppressant, including response to resistant microorganisms. This study is a descriptive review, having as aim to approach the main benefits of endophytic fungi for host plants, as well as the biotechnological application of the bioactive compounds produced by them. The prospection of endophytic in extreme environment could result in discovery of new bioactive compounds with surprising potential for biotechnology area. So, the development of new research frontiers in this issue is indispensable for the sustainable exploitation of the great benefits that these microorganisms could provide to the science.